The impact of SIGN glaucoma guidelines on false-positive referrals from community optometrists in Central Scotland. Issue 3 (18th May 2018) - Sii, Samantha; Nasser, Ahmad; Loo, Cheng Yi; Croghan, Catherine; Rotchford, Alan; Agarwal, Pankaj Kumar
Abstract : Background: Since the introduction of National Institute for Health and Care Excellence glaucoma guidelines 2009, the number of referrals from community optometrists to hospital eye services has increased across the UK, resulting in increase in first visit discharge rates (FVDRs). Aim: To assess the impact of Scottish Intercollegiate Guidelines Network (SIGN) 144 on quality of referrals from community optometrists. Methodology: A retrospective study of patient records who attended as new adult glaucoma referrals to clinics in Princess Alexandra Eye Pavilion, Edinburgh, and in Greater Glasgow and Clyde, was carried out across October–November 2014 (group 1) and September–October 2016 (group 2), before and after the introduction of SIGN 144. The primary outcome of this study is FVDRs. A secondary outcome is the extent of compliance to referral recommendations by SIGN guidelines. Results: Three hundred and twelve and 325 patients were included in groups 1 and 2, respectively. There was a significant decline in FVDRs between these two periods from 29.2% to 19.2%. ( p= 0.004) (OR 0.58 (95%CI 0.40 to 0.84)). Post-SIGN guidelines, 87% of referrals were compliant to SIGN referral criteria while 13% remained non-compliant. The main reasons for non-compliance were no repeatable visual field defects (42.0%) and referrals due to high intraocular pressure were either not repeated or not interpreted in the context of age and central corneal thickness (36.8%). Conclusion: Patients referred after the introduction of SIGN guidelines were 33.5% less likely to be discharged at the first visit. Although compliance to most recommendations in SIGN guidelines has improved, there is still a need to improve adherence to referral criteria